Designing an E-Recruitment Information System Using Simple Additive Weighting Method for Employee Recruitment in Banking Industry - Pramudito, Dendy K; Ahmad, Nazaruddin; Suwanda, Rizki; Zakaria, Muhammad; Judijanto, Loso (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to find out how to design and build an employee e-recruitment information system using the simple additive weighting method. There are three types of data collection methods in this research: observation, interviews, and literature study. The system development method used in this research is the OOAD (Object-Oriented Analysis and Design) method with the rapid application development model, while the tools used in object modeling are UML (Unified Modeling Language). From the discussion that has been described, the following conclusions can be drawn: This e-recruitment information system was designed and built using the RAD system development method and the SAW method for calculations in decision-making, using the PHP and MySQL programming languages as the database, and tested with black box testing. By using the e-recruitment information system to recruit employees, the HR and general divisions have a reference for selecting which prospective employees most closely match the predetermined criteria. This e-recruitment information system can reduce the possibility of human error occurring during the selection process, and with the value of each applicant calculated in the system, it will become a reference for HR staff in selecting employees more objectively. The administrative selection process, which takes one month, can be reduced to a maximum of seven working days. With the e-recruitment information system, selection results that were previously reported via message can now be seen directly in each applicant's account at a predetermined time.